Perancangan Interaksi Aplikasi Tes Minat Bakat Daring untuk Firma Psikologi Jejak Kaki dengan Metode Goal-Directed Design - Pamostang William Richard Hamonangan; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The Covid-19 pandemic has had a great effect on mankind. The presence of the virus has created a shift in how we live, which has affected the economic sector among many others. In order to decrease or even hopefully prevent the spread of the virus, governments across the world have enforced distancing rules. These rules demand adaptation from schools, universities and businesses, creating new-age terms such as remote work or working from home, and so that businesses may continue to operate. The purpose of this research is to create an interaction design of a product which can aid Jejak Kaki Psychology Firm in running their business in current conditions. The research follows the Goal-Directed Design (GDD) methodology, which helps in designing the system for the Online Aptitude Test, abbreviated as TMB-D (in Indonesian), according to the stakeholders' needs. The first phase of GDD is data collection, where it is done via observation with the contextual inquiry method, as well as conducting traditional interviews. Afterwards in GDD methodology is the mapping of the stakeholders' needs as well as the creation of models based off the procured data. Step 3 of GDD is where the researcher defines the framework of research, which is then followed by the last step which is to create a low-fidelity prototype which undergoes usability evaluation. In the outcome of the evaluation, it is discovered that the client interface prototype doesn't require significant alterations, while the psychologist interface prototype requires modifications to ease usage and navigation for the psychologists.